Peran Ekologi Media dalam Media Sosial The 21st IFRA Business Expo 2023 - Winarso, Sebastian Raynaldi; Pribadi, Muhammad Adi (Kiwari, 2024)
Social media has become a very influential platform in disseminating information and promoting events. In this context, the concept of media ecology emerged as a framework for understanding the complex interactions between social media, users, and event content. This study aims to analyze how media ecology plays a role in promoting an event through social media. Through a qualitative approach, this research involves analyzing the content of various social media platforms used to promote certain events. In addition, interviews with social media users and event managers were also conducted to understand their perceptions and experiences in the social media ecosystem. The research results show that media ecology in social media plays a key role in creating mutually beneficial interactions between users, platforms and event content. Social media users actively contributed to spreading information about the event, using features such as hashtags, images and videos and collaborating with influencers to increase visibility. Social media platforms, on the other hand, provide space for various types of promotional content and facilitate interaction between users. By leveraging complex interactions between users, platforms, and content, event organizers can create more effective and impactful promotional campaigns. This research provides in-depth insight into the dynamics of the media ecology in promoting The 21st IFRA Business Expo 2023 via social media, providing a basis for developing smarter promotional strategies in the future Media sosial telah menjadi platform yang sangat berpengaruh dalam menyebarkan informasi dan mempromosikan acara-acara. Dalam konteks ini, konsep ekologi media muncul sebagai kerangka kerja untuk memahami interaksi kompleks antara media sosial, pengguna, dan konten acara. Studi ini bertujuan untuk menganalisis bagaimana ekologi media berperan dalam mempromosikan sebuah acara melalui media sosial. Melalui pendekatan kualitatif, penelitian ini melibatkan analisis konten dari berbagai platform media sosial yang digunakan untuk mempromosikan acara tertentu. Selain itu, wawancara dengan pengguna media sosial dan pengelola acara juga dilakukan untuk memahami persepsi dan pengalaman mereka dalam ekosistem media sosial. Hasil penelitian menunjukkan bahwa ekologi media dalam media sosial memainkan peran kunci dalam menciptakan interaksi yang saling menguntungkan antara pengguna, platform, dan konten acara. Pengguna media sosial secara aktif berkontribusi dalam menyebarkan informasi tentang acara, menggunakan fitur-fitur seperti hashtag, gambar, dan video dan berkolaborasi dengan para influencer untuk meningkatkan visibilitas. Platform media sosial, di sisi lain, menyediakan ruang untuk berbagai jenis konten promosi dan memfasilitasi interaksi antarpengguna. Dengan memanfaatkan interaksi yang kompleks antara pengguna, platform, dan konten, penyelenggara acara dapat menciptakan kampanye promosi yang lebih efektif dan berdampak. Penelitian ini memberikan wawasan mendalam tentang dinamika ekologi media dalam mempromosikan acara The 21st IFRA Business Expo 2023 melalui media sosial, memberikan dasar untuk pengembangan strategi promosi yang lebih cerdas di masa depan.